Self Esteem as a Predictor of Fear of Negative Evaluation and Social Anxiety - Sarwat Jahan Khanam, Fazeela Moghal (Pakistan Journal of Psychology, 2012)
The study aimed to investigate the relationship of self esteem with fear of negative evaluation and social anxiousness. It was hypothesized that self esteem will predict fear of negative evaluation and social anxiety. For this purpose a sample was recruited from various departments of University of KarachiPakistan, consisting of 76 participants (22 males and 54 females), with age ranging from 18 to 29 years. Rosenberg Self Esteem Scale (Rosenberg, 1965), Brief Fear of Negative Evaluation Scale (Leary, 1983) and Interaction Anxiousness Scale (Leary, 1983) were administered to assess the study variables. Linear Regression Analysis revealed that the variable of self esteem is a significant predictor of fear of negative evaluation and social anxiety. It can be concluded that positive self-esteem protects and facilitates better health, positive social behavior and safeguards against the impact of negative influences. Present research will help mental health professionals in developing effective strategies for enhancing self esteem in people thereby dealing with lack of confidence and fear of critical evaluation in social situations.